2021
DOI: 10.3390/ijerph182111273
|View full text |Cite
|
Sign up to set email alerts
|

Access to Assistive Technology during the COVID-19 Global Pandemic: Voices of Users and Families

Abstract: The SARS COVID-19 pandemic emerged in 2019 and has impacted people everywhere. Disparities in impact and outcomes are becoming apparent for individuals and communities which go beyond the trajectory of the disease itself, influenced by the strength and weaknesses of systems of universal health care, and the actions of civil society and government. This article is one of a series exploring COVID-19-related experiences of assistive technology (AT) users across the globe and implications for AT systems strengthen… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
11
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 25 publications
(11 citation statements)
references
References 46 publications
0
11
0
Order By: Relevance
“…See more at: www.who.int/news/ item/28-02-2022-access-to-assistive-tech nology-during-the-covid-19-pandemic Even though there have been calls by AT users and their families for inclusive pandemic responses which encompass their needs across the lifespan, from very young to very old, the activities to help them continue. Layton et al (2021) reported that the AT ecosystem analysis was carried out using the World Health Organization GATE 5 P framework of -People, Products, Personnel, Provision and Policy.…”
Section: Assistive Technologies To Childrenmentioning
confidence: 99%
“…See more at: www.who.int/news/ item/28-02-2022-access-to-assistive-tech nology-during-the-covid-19-pandemic Even though there have been calls by AT users and their families for inclusive pandemic responses which encompass their needs across the lifespan, from very young to very old, the activities to help them continue. Layton et al (2021) reported that the AT ecosystem analysis was carried out using the World Health Organization GATE 5 P framework of -People, Products, Personnel, Provision and Policy.…”
Section: Assistive Technologies To Childrenmentioning
confidence: 99%
“…The emergence of additional access barriers is illustrated from the following quote from a participant in a recent study ( Layton et al, 2021 ): I need someone to hold me when I stand. This made me not able to be supported by someone when I stand up due to social distancing.…”
Section: Covid-19 and Additional Access Barriersmentioning
confidence: 99%
“…Over the course of 2020 and 2021, the inability to obtain AT undoubtedly caused much harm. People with disabilities interviewed on this issue reported similar experiences with their ability to obtain personal assistance services ( Layton et al, 2021 ).…”
Section: Covid-19 and Assistive Technologymentioning
confidence: 99%
“…For example, during the pandemic, assistive technology users responded to a worldwide survey. Most respondents described how service delivery and technology maintenance issued were worsened (Layton et al, 2021). Overall, even for those providers with training and expertise, studies described the need for improved capacity during the pandemic (Puli et al, 2021; Smith et al, 2020).…”
Section: Introductionmentioning
confidence: 99%